How Important Learning Media for In-Service Science Teacher - Permana, Handjoko; Fauzi Bakri; Dewi Muliyati; Mutoharoh; Putri Marsha Sabrina; M. Rizki Diva M; Siti Rachmawati; Gustama Wibawa R (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2024)
This training on developing STEM-based teaching modules aims to equip science teachers with the knowledge and tools needed to create teaching materials, such as modules, that will be used in classroom learning. The development of modules is not only relevant to the curriculum but also capable of integrating STEM concepts. This STEM-based teaching module can enhance critical thinking skills and foster students' creativity to face the challenges of the 21st century. The method in this training session began with the presentation of material on STEM education, guidelines for module development, explanations of examples and types of teaching modules, and provided teachers with the opportunity to collaborate or discuss with the facilitators. Because the module that has been developed is expected to integrate STEM concepts into learning materials both in the classroom and during independent study.  Thus, in this training, it is hoped that it can have a positive impact on both teachers and students so that it can be implemented effectively in the classroom with a more interactive and innovative approach, thereby increasing students' interest in learning and enhancing their ability to solve complex problems.